2006
DOI: 10.1002/macp.200500546
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Sequential Crystallization and Morphological Evolution of Well‐Defined Star‐Shaped Poly(ε‐caprolactone)‐b‐poly(L‐lactide) Block Copolymer

Abstract: Summary: Well‐defined star‐shaped poly(ε‐caprolactone)‐b‐poly(L‐lactide) copolymers (PCL‐b‐PLLA) were synthesized via sequential block copolymerization, and their molecular weights and arm length ratio could be accurately controlled. Both differential scanning calorimetry and wide angle X‐ray diffraction analysis indicated that the crystallization of both the PLLA and PCL blocks within the star‐shaped PCL‐b‐PLLA copolymer could be adjusted from the arm length of each block, and both blocks mutually influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
65
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 33 publications
11
65
0
Order By: Relevance
“…Another interesting observation is the absence of the typical cold crystallization peak of PLLA block during heating, which has been usually reported for PLLA block copolymers. [20][21][53][54] The appearance of this peak depends on the length of the PLLA block, copolymer composition and cooling conditions. Since the cooling rate employed here was very low (1 ºC min -1 ), the PLLA block is able to crystallize until saturation under this condition and additional crystallization does not occur during the heating scan.…”
Section: Saxs Characterization Of the Peo-b-pcl-b-plla Triblock Terpomentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting observation is the absence of the typical cold crystallization peak of PLLA block during heating, which has been usually reported for PLLA block copolymers. [20][21][53][54] The appearance of this peak depends on the length of the PLLA block, copolymer composition and cooling conditions. Since the cooling rate employed here was very low (1 ºC min -1 ), the PLLA block is able to crystallize until saturation under this condition and additional crystallization does not occur during the heating scan.…”
Section: Saxs Characterization Of the Peo-b-pcl-b-plla Triblock Terpomentioning
confidence: 99%
“…2,7,10,47 In many PEO-b-PCL, PCL-b-PLLA and PEO-b-PLLA diblocks copolymers, morphological changes with temperature and composition have been observed: from well-defined Maltese cross spherulites and concentric spherulites to spherulites with continuous banding extinction patterns. 29,33,47,51,53 For instance, PEO-b-PLLA diblock copolymers with PLLA content between 71 and 32 % exhibit PLLA banded spherulites. 52 However, based on the observations of Huang et al 51 in the same diblock copolymers, the branching morphology developed as PLLA content in the terpolymers is lower (see Fig 8a, left) might be a result of the richer PCL-PEO amorphous phase that surrounds the proximity of the PLLA lamellae and disturbs further growth in their immediate vicinity.…”
Section: Morphology Of the Peo-b-pcl-b-plla Triblock Terpolymersmentioning
confidence: 99%
“…[23][24][25] However, in the system of block copolymers, 17,26,27 the formation of banded texture of PLLA become quite complicated because of the strong molecular interaction, microphase separation and constrained geometry of each block, which make the investigations on banded spherulites of the block copolymers consisting of PLLA blocks are still under discussion and not yet claried up to now. Moreover, considering the structural diversity of the block copolymers and the above literature review, there is still lack of intuitive cognition about the banded spherulites of PLLA-PCL copolymers, and no results have been reported on the block length ratio and crystallization temperature on crystalline morphology of PLLA blocks.…”
Section: Introductionmentioning
confidence: 99%
“…13 Aerward, Castillo et al investigated the crystallization kinetics and morphology of PLLA and PCL blocks within a series of PLLA-PCL double crystalline diblock copolymers and found that the reorganization ability of the PLLA block increased with PCL content. 16 Wang et al synthesized well-dened star-shaped PCL-PLLA copolymers and founded that the band spherulites with no obvious Maltese cross patterns were formed, 17 but the detailed formation mechanism of the banded texture of PLLA within the star-shaped PCL-PLLA copolymer was not analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Stannous octanoate [Sn(Oct) 2 ] is the most widely used catalyst for SPCLs. [12][13][14][15][16][17] Nevertheless, high temperature (around 120 C) is always needed for the polymerization. Furthermore, Sn(Oct) 2 is extremely air and moisture sensitive.…”
Section: Introductionmentioning
confidence: 99%